Analysis of Variance of the Effects of a Project’s Location on Key Issues and Challenges in Post-Disaster Reconstruction Projects - Ismail, Dzulkarnaen; A. Majid, Taksiah; Roosli, Ruhizal (MDPI, 2017)
After a disaster, the reconstruction phase is driven by immediate challenges. One of the main challenges in the post-disaster period is the way that reconstruction projects are implemented. Reconstruction cannot move forward until some complex issues are settled. The purposes of this research are to highlight the issues and challenges in post-disaster reconstruction (PDR) projects and to determine the significant differences between the issues and challenges in different locations where PDR projects are carried out. The researchers collected data within international non-governmental organisations (INGOs) on their experience of working with PDR projects. The findings of this research provide the foundation on which to build strategies for avoiding project failures; this may be useful for PDR project practitioners in the future.